DESIGN OF AUTOMATIC STAMPING MACHINE FOR DATE AND DASH CODE MARKING USING PNEUMATIC SYSTEM AND PLC CONTROLLER - Nanang Ali Sutisna; Reza Alfarisi Firmansyah (Journal of Mechanical Engineering and Mechatronics, 2018)
The research is meant to design an automatic machine for stamping the date and dash code on the master carton for the packaging of the blister-pack. The quantity of existing manual process in producing the master carton does not meet with the demands, therefore, it needs a machine that improve the production process with the following characteristic: fast, easy to use and maintain, and also affordable in order to support the cost saving program. The design uses pneumatic system with PLC controller to automate the process.